RANCANG BANGUN FLEXY BIKE SEBAGAI ALAT TRANSPORTASI ALTERNATIF KELUARGA INDONESIA - Djumhariyanto, Dwi (ROTOR, 2013)
Bicycle (human powered vehicles) is very popular transportation appliance in society, with all excess and its insuffiency. Design bicycle specially form and its size measure adapted for ergonomi of bodyÂ  human being with the certain age, its meaning minibike just to children, while big bicycle just to adult or child with the high body. So that is not rarely met, at one particular family own some bicycle type, as according to its wearer. as a result required a broader place many for the menyimpan of bicycle. This matter enough become the big problem in cities, where farm for the house of progressively narrow. To finish the problem, this research designed and made by a bicycle which can be used by all age (except baby), the bicycle Flexy Bike. Flexy Bike is bicycle having function fleksible. That is bicycle which can be functioned in so many form and size measure, without lessening security and its freshment. Others, Flexy Bike designed to can be folded, so that earn easily kept without requiring wide place.Â Keywords: bicycle, scheme, flexible and Flexy Bike